Interoception, personality, and internet use: Preliminary insights into their association - Dovile Simkute; Grace Y. Wang; Inga Griskova-Bulanova (PLoS ONE, 2025)
Problematic Internet Use (PIU) is increasingly recognized as a concern among internet users, prompting investigations into the factors that may predispose individuals to PIU. Interoceptive awareness, one of cognitive-perceptual factors, refers to the ability to perceive internal bodily sensations and has been shown to play a significant role in the onset and maintenance of drug addiction. However, its relationship with PIU remains underexplored. This study aimed to investigate the dimensions of interoceptive awareness within the context of PIU and to explore the role of personality traits in their relationships in a non-clinical sample of regular internet users. Involving 161 participants (71 males), the PIUQ-9 (Nine-Item Problematic Internet Use Questionnaire), DPIU (Dimensions of Problematic Internet Use), Neo-Pi-R NEO (Personality Inventory-Revised) and MAIA (Multidimensional Assessment of Interoceptive Awareness) questionnaires were employed. Spearman correlations and network analysis were conducted to assess relationships and interconnections among the variables. Neuroticism emerged as a central factor, strongly linked to both PIU and interoceptive awareness. Network analysis highlighted specific negative connections between the interoceptive states of Trusting and Not-Distracting and PIU. These preliminary findings suggest that certain interoceptive dimensions and personality traits, particularly neuroticism, are significantly associated with PIU. This study contributes to the field by highlighting interoceptive dimensions as relevant factors in understanding PIU and emphasizes the scarcity of research in this area, encouraging further investigation to address this gap.